Low Doses of Radiation Reduce Risk - R. E. J. Mitchel (SAGE Publishing, 2007)
The "Linear No Threshold" hypothesis, used in all radiation protection practices, assumes that all doses, no matter how low, increase the risk of cancer, birth defects and heritable mutations. In vitro cell based experiments show adaptive processes in response to low doses and dose rates of low LET radiation, and do not support the hypothesis. This talk will present cellular data and data from animal experiments that test the hypothesis in vivo for cancer risk. The data show that a single, low, whole body dose (less than about 100 mGy) of low LET radiation, given at low dose rate, increased cancer latency and consequently reduced both spontaneous and radiation-induced cancer risk in both genetically normal and cancer-prone mice. This adaptive response lasted for the entire lifespan of all the animals that developed these tumors, and effectively restored a portion of the life that would have been lost due to the cancer in the absence of the low dose. Overall, the results demonstrate that the assumption of a linear increase in risk with increasing dose in vivo is not warranted, and that low doses actually reduce risk.